Perception of nursing workers on the care of hypertension in older adult - Rosimeire Fontes de Queiroz; Angela Maria Alvarez; Luana Jordana Morais; Richardson Augusto Rosendo da Silva
ABSTRACT Objective: To understand how nursing workers perceive care of hypertension (HBP) in older adult within the scope of the Family Health Strategy. Method: A qualitative descriptive study carried out in the city of Natal/RN, with 20 nursing workers providing care to older adults with HBP. The data were obtained through a semi-structured interview and analysed by the Thematic Analysis, based on the theoretical support of the integrality, using Atlas.ti 7.0 software. Results: The elements found as facilitators were: territorialization, partnerships, professional proactivity and the user's bond with the team. Among those found as barriers were: disease-centered care; academic education based on the biomedical model; lack of inter-sectorality and discontinuity of care in the care network. Final considerations: Nursing workers perceive that health institutions lack articulated and innovative practices that incorporate new paradigms focused on integrality of care.